2002
DOI: 10.1107/s1600536802005111
|View full text |Cite
|
Sign up to set email alerts
|

9-(tert-Butylamino)acridine

Abstract: The crystal structure of 9‐(tert‐butyl­amino)­acridine, C17H18N2, is composed of mol­ecules of the amino tautomeric form. The acridine moiety is slightly folded along the C⋯N line passing through opposite atoms of the central ring, and the orientation of the tert‐butyl­amino group makes the conjugation between the lone pair of the N atom and the acridine π‐system almost negligible. An intermolecular hydrogen bond, involving the exocyclic NH group as donor and the endocyclic N atom as acceptor, links the mol­ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Table 1 gives parameters characterizing the geometries of the central acridine ring and the ester group. These are typical of acridine-based derivatives (Hempel et al, 1979;Meszko et al, 2002;Mrozek et al, 2002;Sikorski et al, 2005).…”
Section: Commentmentioning
confidence: 96%
See 1 more Smart Citation
“…Table 1 gives parameters characterizing the geometries of the central acridine ring and the ester group. These are typical of acridine-based derivatives (Hempel et al, 1979;Meszko et al, 2002;Mrozek et al, 2002;Sikorski et al, 2005).…”
Section: Commentmentioning
confidence: 96%
“…Since the phenyl fragment is removed during the oxidation of these compounds, it has been hypothesized that the phenyl ring substituents exert the greatest influence on the stability of 9-carboxy-10methylacridinium phenyl esters and their ability to chemiluminescence (Sato, 1996;Rak et al, 1999). Despite the long interest shown in this group of compounds, there are only two publications (by our own research team) on the crystallography of alkylphenyl-9-carboxylates (Meszko et al, 2002;Sikorski et al, 2005). It is thus important to extend investigations to further representatives of this group, especially in view of the fact that information on the structure, crystal packing and other features may help in the design of hydrolysis-resistant compounds able to react efficiently with oxidizing agents to produce light.…”
Section: Commentmentioning
confidence: 99%
“…1.7 (3) À4.0 1.0 (3) 22.3 2Notes: (I) 9-(trichloroacetylimino)acridine monohydrate (this work); (II) 9-acridinamine hemihydrate (Chaudhuri, 1983); (III) 9-(tert-butylamino)acridine (Meszko et al, 2002); (IV) 9-(phenylamino)acridine (Leardini et al, 1998); (V) 9-(dimethylamino)acridine (Rak et al, 1998); (VI) 10-methyl-9-(methylimino)acridine (Rak et al, 1998 (Kuma, 1989); cell refinement: KM-4 Software; data reduction: KM-4 Software;…”
Section: Tablementioning
confidence: 98%
“…Theory also predicts the co-existence of tautomeric forms in 9-aminoacridines monosubstituted at the exocyclic N atom (Rak et al, 1998). The structures of only two such derivatives have been determined, namely 9-(tert-butylamino)acridine (Meszko et al, 2002) and 9-(phenylamino)acridine (Leardini et al, 1998). It was found that crystals of these compounds are composed of molecules of the amino tautomer.…”
Section: Commentmentioning
confidence: 99%
“…Table 1 gives parameters characterizing the geometries of the central acridine ring and the ester fragment. They are typical of acridine-based derivatives (Hempel et al, 1979;Meszko et al, 2002;Mrozek et al, 2002;Sikorski et al, 2005).…”
Section: Commentmentioning
confidence: 99%